Interrelationship between altered metabolites and the gut microbiota in people living with HIV with different immune responses to antiretroviral therapy - Xuebin Tian; Zhongyao Gao; Yiwen Xie; Xiangyun Lu; Yulong Zhao; Peng Yao; Mingqing Dong; Lifeng Yu; Nanping Wu (Current Research in Microbial Sciences)
Background: Antiretroviral therapy (ART) effectively reduces opportunistic infections and mortality in people living with HIV (PLWH); however, some patients exhibit poor immune recovery. This study explores the connections among immune responses, metabolites, and the gut microbiota in PLWH with differing reactions to ART. Methods: We analyzed the gut microbiota composition, metabolites, and immune markers in 38 PLWH who showed an immunological response (IR) and 32 who did not (INR), as classified according to CD4+ T-cell levels after 24 months of ART. Additionally, in vitro assays using cell counting kit 8, flow cytometry, and quantitative real-time reverse transcription PCR were employed to assess the effects of the metabolites on cell viability, immune marker expression, and cytokine levels. Results: Gut microbiota and metabolic profiles differed significantly between the IR and INR groups. Enterococcus was more abundant in the INR group, whereas [Ruminococcus]_gnavus_group levels were reduced. Significant metabolic pathway alterations included decreased folate biosynthesis and biotin metabolism. We observed negative associations of Parabacteroides with activation markers on CD4+ T-cells, and positive correlations with CD4/CD8 ratios. Enterococcus showed inverse relationships with these markers. Indole-3-acetyl-beta-1-D-glucoside (area under the curve value = 0.8931), had the best discriminatory ability. Further experiments showed that Indole-3-acetyl-beta-1-D-glucoside significantly decreased the proportions of CD4+CD57+, effector CD4+, CD4+PD1+, CD8+CD57+, effector CD8+, and CD8+HLA-DR+ T cells. Moreover, mRNA expression analysis showed that Indole-3-acetyl-beta-1-D-glucoside treatment led to a suppression of pro-inflammatory cytokines. Conclusion: The multi-omics approach highlighted potential biomarkers for immune recovery in HIV, suggesting avenues for further research into treatment strategies.